2017
DOI: 10.1093/ecco-jcc/jjx002.541
|View full text |Cite
|
Sign up to set email alerts
|

P416 Real world data on the effectiveness and safety of vedolizumab in the treatment of Crohn's disease and ulcerative colitis: the Edinburgh experience

Abstract: Results: Of the 55 included children, 33 (60%) had UC/IBDU, and 22 (40%) had Crohn's Disease (CD); [28 (51%) male, mean age at first VDZ dose 14.5±2.8 years, and median disease duration 3.5 years (IQR 1.8-5.1)]. All were previously treated with anti-TNF (27% primary failure, 49% secondary failure, 15% adverse reaction and 9% for other reasons) and 8 (15%) had prior surgical intervention. Success rates at week 14 were 21% in UC, and only 9% in CD (p=0.24). Median follow-up period was 22 weeks (IQR 14-22) from V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…From the Netherlands, endoscopic response to vedolizumab therapy was observed in 8/15 (47%) patients with CD and 9/11 (82%) patients with UC, but the clinical remission rates were < 50% in both CD and UC . In Scotland, 340 patients (203 CD and 137 UC) experienced lower hospitalization rates and steroid usage associated with vedolizumab treatment . In Spain, a study of 274 patients (144 CD and 130 UC) identified that vedolizumab was more likely to be effective in UC than CD, if the patients were anti‐tumor necrosis factor naïve and if they had mild or moderate disease, instead of severe disease .…”
mentioning
confidence: 99%
“…From the Netherlands, endoscopic response to vedolizumab therapy was observed in 8/15 (47%) patients with CD and 9/11 (82%) patients with UC, but the clinical remission rates were < 50% in both CD and UC . In Scotland, 340 patients (203 CD and 137 UC) experienced lower hospitalization rates and steroid usage associated with vedolizumab treatment . In Spain, a study of 274 patients (144 CD and 130 UC) identified that vedolizumab was more likely to be effective in UC than CD, if the patients were anti‐tumor necrosis factor naïve and if they had mild or moderate disease, instead of severe disease .…”
mentioning
confidence: 99%